PERBEDAAN GENDER DAN GAYA KOMUNIKASI PENCERAMAH DALAM PROGRAM TRANS TV ISLAM ITU INDAH - Halimatun Syakdiah, Yulia Warda, Rukmana Prasetyo, (Taushiah: Jurnal Hukum, Pendidikan dan Kemasyarakatan, 2022)
Gender differences are differences in characteristics between men and women that are formed in the interaction relationship. So gender represents the social and cultural roles of men and women, not the physical form of men and women. Furthermore, in the communication style proposed by Tannen: 1992, there are six different ways that male and female speakers are presented. Such as Status versus Support, independence versus intimacy, advice versus understanding, Information versus feeling, orders versus proposal, conflict versus compromise. Even though men and women have the same language, they have different ways and attitudes of communication in their interactions, this is motivated by socio-cultural factors. In line with Danil Maltz and Borker stated that boys and girls have different social spheres in society. For example, in the public sphere, male speakers show more power than women, while female speakers refrain from expressing their power in the public sphere. The purpose of this study, 1) to describe the differences in the communication styles of male and female lecturers in the Trans Tv Islam program is Indah. 2) To find out why male and female lecturers have different communication styles in the Trans Tv Islam Itu Indah program. In this case, whether male and female speakers have different communication styles or have the same communication style strategy. As for the data collection techniques that include observation and documentation, this study uses a qualitative multicase study consisting of two male lecturers and two female lecturers. Furthermore, there are three models in data analysis, namely data reduction, data display and conclusion drawing. Based on the analysis, it was found that female lecturers can communicate like the communication style of male lecturers, whereas male lecturers can communicate like the communication style of female lecturers. And also the reason why male and female speakers have different communication styles because they have their own characteristics in their culture and social life.